Effects of middle-aged and elderly people’s self-efficacy on health promotion behaviors: Mediating effects of sports participation - Chen, Nan; Zhang, Jia; Wang, Zhiyong (Frontiers in Psychology, 2023)
Objective: This study explores the relationship among self-efficacy, sports participation, and health promotion behavior for the middle-aged and elderly. Therefore, it provides a theoretical reference for improving the quality of life for middle-aged and elderly adults and promoting a healthy lifestyle for the elderly. Methods: 591(male: 36.2%, female: 63.8%; age: above 50) middle-aged and elderly adults from five cities of Henan Province were selected as the research objects by convenient sampling. The self-efficacy, sports participation, and health promotion behavior scales were used for the questionnaire survey. Amos24.0 was used to test the structural equation model, intermediary function test, and bootstrap analysis. Results: The self-efficacy of middle-aged and elderly people positively impacted health promotion behavior. The path coefficient was 0.439. Sports participation played a partial intermediary role between self-efficacy and health promotion behavior（χ2/df=1.785, RMSEA=0.036, RMR=0.021, GFI=0.967, CFI=0.976, TLI=0.971) The proportion of intermediary effect was 26.34% (0.100, 0.225). Conclusion: 1) Self-efficacy can significantly and positively affect health promotion behavior for middle-aged and elderly people; 2) Sports participation plays a partial intermediary role between self-efficacy and health promotion behavior. From this part of a view, we can enhance the self-efficacy of middle-aged and elderly people and improve their healthy life behavior by advancing sports participation. Thus, it provides theoretical support and practical guidance for promoting national health.